Riscos e oportunidades da unificação monetária no mercosul (a teoria de áreas monetárias ótimas e a União Monetária Européia como Referências) - Consentino, Fernanda Mazzeo Ribeiro (2005)
The work seeks to evaluate the feasibility of monetary integration at Mercosur based on the Optimun Currency Area Theory and on the European Monetary Union experience. We realize Mercosur does not join the necessary conditions to form a monetary union yet. We do not believe it is an ultimate result, though. The modern Optimum Currency Area Theory is based on a dinamic analysis of the integration process, what allows a region to become an optimum currency area ex-post. Moreover, constituting a monetary union at Mercosur depends mainly on political will, which is influenced by perspectives of economic and social development and a better position in the international scene for Mercosur countries. The lattest facts points to a considerable interest of political class in this direction